Harmony of Monotheism in Becekan Rajab: Exploration of Islamic Education Values in the Mystical Tradition of Javanese Society - Sulestri; Aziz, Abdul; Fathurohman, Mohamad; Hayati, Nur Rohmah; Ihtiari, Dhiya Ayu Tsamrotul (Jurnal Pendidikan Multikultural Indonesia, 2023)
The society's beliefs in Java regarding traditions related to Islamic education values can be diverse and complex due to Java's rich cultural and historical background with various beliefs. Therefore, it is important to note that each group or community in Java may have different perspectives on traditions and Islamic educational values. This research aims to analyze the history, process, and Islamic educational values found in the Becekan Rajab tradition in Javanese society. The research uses a qualitative method with field research. The results of the study show that the Becekan tradition historically originated from the instinct of an ancestor named Mbah Pucet, the first Village Head of Kaliwungukidul Ngombol Purworejo, around 1930. This tradition is part of the village's traditional ritual or village cleansing, which is held every 27th of Rajab. The series of the Becekan tradition ceremony begins with cleaning the graves, slaughtering a goat at the gravesite, reciting Yasin Tahlil, and holding religious lectures. Islamic educational values present in the Becekan tradition include values of faith, ethics, appreciation for knowledge, humanity, balance, and compassion for all (rahmatan lil’alamin). This research can help Javanese communities understand the Becekan tradition more deeply, including its history, implementation process, and the values it contains. It can broaden people's awareness of local traditions and strengthen their cultural identity.